STRATEGI PENGEMBANGAN OBJEK WISATA UNGGULAN HAPANASAN OLEH DINAS KEBUDAYAAN DAN PARIWISATA ROKAN HULU - Aini, Hurul; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Development of flagship object tourist Hapanasan important done. Every object tourist thatdeveloped, built, and managed properly will increase the number of tourists as well as OriginalIncome area. In the implementation of the Development Department of culture and tourism of RokanHulu has a strategy that is, complete facilities and infrastructure repair, improved sights, as well asenhancing community participation. However, the implementation of the development are still notoptimally performed. How the actual implementation of development strategy flagship object touristHapanasan by Department of culture and tourism of Rokan Hulu, and what are the factors affectingthe development of the flagship object tourist Hapanasan by Department of culture and tourism ofRokan Hulu.The concept of the theory used is adaptive strategy researcher, Miles and Snow in Heene (2010)which consists of the technology, the determination of the authorities, coordination, implementationand system settings. This study uses qualitative methods research with descriptive data analysis. Theauthor uses data collection techniques interviews, observation, documentation, and library studies.With the use of Key Informants as a source of information and using the technique of triangulationas a source in the vadilitas test data.Based on the results of the research, strategy development flagship object tourist Hapanasan byDepartment of culture and tourism of Rokan Hulu hasn't been done optimally, since there are stillefforts that have not realized by the Department of culture and tourism of Rokan Hulu in theimplementation of the development. Factors that affect the implementation of the strategy is the lackof funds owned, human resources have not been sufficient good quality as well as quantity, as well asregulatory policies that can support the development of a flagship object tourist does not exist.Keywords: Strategy, Development, Tourist Object